2010
DOI: 10.1148/radiol.09091406
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Upgrade of Atypical Ductal Hyperplasia after Stereotactic Breast Biopsy: Effects of Number of Foci and Complete Removal of Calcifications

Abstract: The upgrade rate is significantly higher when ADH involves at least three foci. Surgical excision is recommended even when ADH involves fewer than three foci and all mammographic calcifications have been removed, because the upgrade rate is 12%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 41 publications
6
44
1
2
Order By: Relevance
“…30.4 % (7/23) of the diagnoses of AEPDT in minimally invasive biopsy were not proved as atypical ductal hyperplasia (ADH) after excision surgery but were upgraded to a malignant diagnosis, mainly to DCIS diagnosis (85.7 %). Kohr et al concluded that surgical excision should be recommended even when ADH involves fewer than three foci and all mammographic calcifications have been removed by needle biopsy, because the upgrade rate was still 12 % [11]. Our results support that finding.…”
supporting
confidence: 88%
“…30.4 % (7/23) of the diagnoses of AEPDT in minimally invasive biopsy were not proved as atypical ductal hyperplasia (ADH) after excision surgery but were upgraded to a malignant diagnosis, mainly to DCIS diagnosis (85.7 %). Kohr et al concluded that surgical excision should be recommended even when ADH involves fewer than three foci and all mammographic calcifications have been removed by needle biopsy, because the upgrade rate was still 12 % [11]. Our results support that finding.…”
supporting
confidence: 88%
“…In the literature, upgrade rate ranges from 0% to 17% (35). Kohr et al (36) found that there were no significant differences in upgrade rates based on whether the determinant mammographic calcifications were completely removed at stereotactic VABB. However, they found that upgrade to DCIS or invasive carcinoma was significantly less likely when ADH involved <3 foci than when it involved ≥3 foci.…”
Section: Discussionmentioning
confidence: 99%
“…Technical advances in percutaneous core needle biopsy, such as increasing needle diameter from 14-gauge to 11-gauge and adding a vacuum device, have allowed larger samples of tissue to be obtained (5,6), substantially improving the accuracy of diagnosis. Despite these improvements, the rate of underestimation for ADH has been reported as 10% to 26% for 11-gauge vacuum-assisted biopsy (VAB) (2,14,(21)(22)(23)(24)(25)(26)(27)(28). In this study, 11-gauge SVAB was associated with a lower rate of underestimation for ADH (20.6%), compared to USguided 14-gauge automated biopsy (41.7%) (P = 0.007).…”
Section: Discussionmentioning
confidence: 85%